2018
DOI: 10.1021/acs.jpcb.8b07506
|View full text |Cite
|
Sign up to set email alerts
|

Water and a Borohydride/Hydronium Intermediate in the Borane-Catalyzed Hydrogenation of Carbonyl Compounds with H2 in Wet Ether: A Computational Study

Abstract: We have computationally evaluated water as an active Lewis base (LB) and introduced the borohydride/hydronium intermediate in the mechanism of B(CF)-catalyzed hydrogenation of carbonyl compounds with H in wet/moist ether. Our calculations extend the known frustrated Lewis pair mechanism of this reaction toward the inclusion of water as the active participant in all steps. Although the definition of the zero-energy point interweaves in comparison of the scenarios with and without water, we will be able to show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Recently, it was found that the free-energy profile may become exergonic through the formation of a particularly stabile "borohydride/hydronium" ion pair intermediate in the presence of water molecules. 58 The results shown in Figure 10 are in agreement with the "Hammond's postulate" that the transition-state structure in an exothermic reaction resembles the reactants and in an endothermic reaction seems like the products. Furthermore, the barrier heights correlate very well with the reaction free energies of H 2 splitting, which is in accordance with the "Bell− Evans−Polanyi (BEP) principle".…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Recently, it was found that the free-energy profile may become exergonic through the formation of a particularly stabile "borohydride/hydronium" ion pair intermediate in the presence of water molecules. 58 The results shown in Figure 10 are in agreement with the "Hammond's postulate" that the transition-state structure in an exothermic reaction resembles the reactants and in an endothermic reaction seems like the products. Furthermore, the barrier heights correlate very well with the reaction free energies of H 2 splitting, which is in accordance with the "Bell− Evans−Polanyi (BEP) principle".…”
Section: Resultssupporting
confidence: 77%
“…Recently, it was found that the free-energy profile may become exergonic through the formation of a particularly stabile “borohydride/hydronium” ion pair intermediate in the presence of water molecules. 58 …”
Section: Resultsmentioning
confidence: 99%